The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1017/s0033291708004613
|View full text |Cite
|
Sign up to set email alerts
|

Impact of stress on paranoia: an experimental investigation of moderators and mediators

Abstract: The results support and specify the role of emotional reactions to stressors on the pathway from vulnerability to psychosis and highlight the relevance of anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
101
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(110 citation statements)
references
References 67 publications
9
101
0
Order By: Relevance
“…Given their similarities it is not surprising that, although social anxiety and paranoia are typically defined as distinct constructs, recent research has found evidence of overlap between them in both psychiatric samples (Fornells-Ambrojo and Garety, 2009) and the general population (Lincoln et al, 2009). Findings from one study suggest that sub-clinical paranoid ideation may be appropriately categorized as a form of anxiety in some individuals (Freeman et al, 2008a); other research similarly links paranoid thoughts more broadly with different types of PERCEPTUAL ANOMALY, SOCIAL ANXIETY, AND PARANOIA 4 negative affect (NA) (Combs et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Given their similarities it is not surprising that, although social anxiety and paranoia are typically defined as distinct constructs, recent research has found evidence of overlap between them in both psychiatric samples (Fornells-Ambrojo and Garety, 2009) and the general population (Lincoln et al, 2009). Findings from one study suggest that sub-clinical paranoid ideation may be appropriately categorized as a form of anxiety in some individuals (Freeman et al, 2008a); other research similarly links paranoid thoughts more broadly with different types of PERCEPTUAL ANOMALY, SOCIAL ANXIETY, AND PARANOIA 4 negative affect (NA) (Combs et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Also, state anxiety was associated to an increase of paranoid beliefs following the presentation of a stressor. Lincoln et al [3] thus argued that state anxiety feelings may lead to paranoid beliefs hence giving support to Freeman and Garety's argument that anxiety is the link between neurosis and psychosis. Furthermore, there are studies that appear to suggest that paranoia is associated to both negative emotion and an aggressive temperament (Campbell and Morrison, 2007).…”
Section: Introductionmentioning
confidence: 95%
“…investigated a causal relationship for the establishment of depressogenic symptoms or moods that included the attributional diathesis (internal locus) x failure (external locus) interaction; see Metalski, Joiner, Hardin, & Abramson's, 1993 reformulated model of hopelessness and the mediating effect of self-esteem). Although there are advantages to this method, it is difficult to interpret the causal direction between stress and symptoms due to the complex interactions between the individual and his/her environment in day-to-day life [3]. However in spite of this model's shortcomings and to our knowledge of the literature, there aren't many studies that compare non-clinical paranoid versus socially anxious individuals's paranoid and emotional reactions to failure, which therefore shows the importance of studying not only situations of environmental stress but in particular social stress and also situations of negative social evaluation and loss of rank and their relationship to paranoia.…”
Section: Social Anxiety Group (Sag)mentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence for the necessity of this view comes from many findings, including those on the impact of stress 20 or walking through an urban lansdcape 21 on symptoms such as paranoia and anxiety, as well as on the links between understimulating environments and expression of negative symptoms. 22 Problem-oriented medical information systems allow treatment planning to be organized around disordered pathophysiological processes, behavioral domains, and environmental stressors, and these approaches need evaluations for cost-benefits determinations.…”
Section: Theme 4: What Is Necessary To Enhance Development and Utilizmentioning
confidence: 99%